business developMent using carob in the coMMunity association “sequion olMos” - Espinoza, José (2014)
“Sequion Olmos” is an association belonging to the Rural Community Santo Domingo de Olmos, located in the district of Olmos province Chiclayo, Lambayeque department; the population is rural customs and is mainly engaged in agriculture. The Association owns 1,424 hectares of land that is rarely used due to limited financial resources they have. The average household income is US$ 7.00 day. The predominant trees are the “carob”, typical of arid areas and require minimal amounts of water to grow. These trees are used by the people of Sequion Olmos, firewood and / or charcoal, which is causing an accelerated desertification and salinization of soils, which in turn generates increased poverty levels. What is the industrial and economic potential of carob?: as food, fruits are high in protein, sugar, minerals, B vitamins and fiber; algarrobina done with them and with the seed, coffee; fodder, the leaves are eaten by sheep and goats mainly cattle and fruit replaces corn and wheat bran in the diet of animals; In agroforestry, it is used as farm fences, windbreaks and provides shade for livestock; as medicinal use, carob is a powerful natural tonic; Seed alcohol and other natural medicines is obtained; moreover, its flowers are excellent honey producers, jelly, pollen and wax; and decaying leaves are used to make compost. In Peru, from independence to date, has been developing a predatory primary export economy, our resources. Peru has an ethno-rich bio-diversity, which allows for eco-businesses, provide environmental services and develop tourism ecológico. Business with positive environmental and economic performance based on local, ethnic and biological diversity, applying innovations. Globally there is a growing demand for organic, natural products and great concern for global environmental problems: climate change, livelihood diversity, livelihoods of indigenous populations, impacts on the environment. The overall objective of this article is to identify the possibilities for economic development of the Association of commoners “Sequion Olmos” by marketing and / or industrialization of carob trees and their components. The procedure used to evaluate the possibility of undertaking this econegocio was through surveys and interviews. The surveys were conducted to muestreal level and steps taken were: determination of representative sample survey design and corresponding instructions, preparation and training of survey personnel, development of muestreal survey, collection and processing of results, validation results via comparison with primary information sources. The interviews were conducted directly via the paper’s authors meetings with experts in this field relative to handling and management of locust; these were performed in two stages: the first one to establish the general framework of the topic and the second with a sheet of questions and structured type chek list, according to what is required as input for the proper development of the publication. Application of muestreal survey and interviews, we conclude the following: a)The people ignore the many benefits that would bring an orderly exploitation of carob trees that surround them. b)They do not know the ways how marketing and industrialization of carob can bring improvements in the economy, so they are not interested in investing in industrialization or commercialization. c)Lack of awareness of the population about the magnificent potential of carob. The appreciation of the people is only good for use as firewood and charcoal. d)Inadequate Technological application to generate the planting of large forests of carob. e)Weak development of products derived from carob (carob, flour, etc.) f)Current algarrobina producers use 80% machinery and low efficiency craft technology. g)Methods of limited marketing prey mostly just craft fairs to offer products. h)Have started some basic boost consumption of carob snacks in hotel and restaurant activities.